Database Web Server for Customers in BPR Trijaya with using PHP and MySQL - Kurnia Perdana Dwi Putranto (Jurnal Sistem Informasi, 2009)
The database is a very important aspect in information technology, and is a basic component of an information system. Orderrunning application program and database server based, it is necessaryweb application server, the authors make a web database server customershas opened a customer service application to a bank savings account that willcan tehubung to the internet network.Trijaya BPR is a banking financial services companystanding dated October 7, 2004. One of the products and services presentedis the savings to our customers, currently still using the BPR TrijayaMicrosoft Access database as storage facilities. Because compatibilitythe less so nice if accessed through the network until nowmanagement of customer database is still offline.Results from refineries based databases will be an online web serverprovides ease in BPR in terms of distributing Trijayacustomer data at each branch office.Managing an online database will provide benefits forBPR Trijaya owners in building an online service infrastructureat each branch office if accompanied by an understanding. And forcustomer service must also be able to understand the use of the web server facilitiesthe utilization of online databases.